O brabo e a borboleta: a trajetória de Antonio Joze de Mello Brabo, um militar paulista no Planalto Sul-RioGrandense (meados do século XlX) - Bastos Neto, Ernesto Pereira (Universidade do Vale do Rio dos Sinos, 2022)
The present study is an investigation of military recruitment and the formation of military leaderships in the 19th century Rio Grande do Sul. Inspired by Italian micro-history, the scale of observation was reduced, selecting the life of a character as the guiding thread of the research. In the beginning of the 19th century, Antonio Joze de Mello Brabo migrated from a village in the backlands of São Paulo to the south and, over the course of a few decades, became one of the main military commanders settled in the plateau of Rio Grande do Sul . The research aims to understand which social conditions and strategies made this trajectory possible. Although he commanded battalions in successive wars, from Cisplatina (1825-1828) to the war against Paraguay (1864-1870) - which earned him honorary decorations and honorary patents - , the trajectory of Antonio Joze de Mello Brabo does not reveal the performance of a rich man of fields and cattle, but a very heterogeneous biography, marked by an economic life no more than average and a very discrete, if not insignificant, political action. The nodal points of his military recruitment capacity seem to be found both in an efficient military performance and in his relational capital, particularly in an ability to negotiate with various local sectors of the society in which he was inserted, in the southern Rio Grande plateau.
Keywords: Antonio Joze de Mello Brabo; Trajetórias militares; Nova História militar; História do Brasil Imperial; Military trajectories; New Military History; Imperial Brazil History; ACCNPQ::Ciências Humanas::História